2019
DOI: 10.1111/medu.13775
|View full text |Cite
|
Sign up to set email alerts
|

Trainees’ perspectives of assessment messages: a narrative systematic review

Abstract: Objectives This study was designed as a narrative systematic literature review of medical specialist trainees’ perspectives of the assessment messages they receive in the context of clinical performance assessments. The aim of the study was to determine if trainees value the information they receive through the formats designed to promote their development and, if not, the reasons for this. Methods The authors searched the ERIC, EMBASE, Ovid MEDLINE and PsycINFO databases for articles published up to 16 June 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 51 publications
0
11
0
Order By: Relevance
“…Workplace-based assessment offers trainees an opportunity for guidance and supervisors the opportunity to judge the trainees' clinical practice. However, many trainees do not see workplacebased assessments as an opportunity to learn but rather a hurdle to be passed [1][2][3] and may alter their practice specifically for these assessments. 4,5 One reason for this inauthenticity may be lack of trust in their supervisor.…”
Section: Discussionmentioning
confidence: 99%
“…Workplace-based assessment offers trainees an opportunity for guidance and supervisors the opportunity to judge the trainees' clinical practice. However, many trainees do not see workplacebased assessments as an opportunity to learn but rather a hurdle to be passed [1][2][3] and may alter their practice specifically for these assessments. 4,5 One reason for this inauthenticity may be lack of trust in their supervisor.…”
Section: Discussionmentioning
confidence: 99%
“…In their systematic review of trainee's perspectives of assessment messages, Scarff et al 34 outline environmental and assessor‐related factors that affect perspectives on feedback, including available time for feedback, enthusiasm for feedback, engagement with the learner, and honesty. This study builds on these findings, demonstrating the interaction between these characteristics with trust, relationship‐building, and their effect on resident mindset, which residents associated with their front stage performances.…”
Section: Discussionmentioning
confidence: 99%
“…This study builds on these findings, demonstrating the interaction between these characteristics with trust, relationship‐building, and their effect on resident mindset, which residents associated with their front stage performances. In their discussion, Scarff posits that learners are polarised into two groups with regards to their interaction with assessment and feedback: learning goal‐oriented vs performance goal‐oriented 34 —these link directly to growth vs fixed mindset. While they describe them as intrinsic characteristics of the learner, we have shown that these characteristics are fluid, even within the individual learner, and are affected by context and relationship within the clinical learning environment.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, recent reviews highlight person al and environmental factors influencing the way trainees perceive the developmental value of assessment, self-motivation also being reported as an important driver of feedback seeking. 17 18 This is a possible reason explaining why previous attempts for gathering such information 8 were felt as incomplete and unreliable. By using a qualitative approach, we were able to combine and report in-depth views of several individuals from different positions and countries.…”
Section: Discussionmentioning
confidence: 99%